It Takes Two to Tango, Part II: Synthesis of A-Ring Functionalised Quinones Containing Two Redox-Active Centres with Antitumour Activities - Joyce C. Oliveira; Renato L. de Carvalho; Hugo G. S. Sampaio; João Honorato; Javier A. Ellena; Felipe T. Martins; João V. M. Pereira; Pedro M. S. Costa; Claudia Pessoa; Rafaela S. Ferreira; Maria H. Araújo; Claus Jacob; et al. (Molecules, 2023)
In 2021, our research group published the prominent anticancer activity achieved through the successful combination of two redox centres (ortho-quinone/para-quinone or quinone/selenium-containing triazole) through a copper-catalyzed azide-alkyne cycloaddition (CuAAC) reaction. The combination of two naphthoquinoidal substrates towards a synergetic product was indicated, but not fully explored. Herein, we report the synthesis of 15 new quinone-based derivatives prepared from click chemistry reactions and their subsequent evaluation against nine cancer cell lines and the murine fibroblast line L929. Our strategy was based on the modification of the A-ring of para-naphthoquinones and subsequent conjugation with different ortho-quinoidal moieties. As anticipated, our study identified several compounds with IC50 values below 0.5 µM in tumour cell lines. Some of the compounds described here also exhibited an excellent selectivity index and low cytotoxicity on L929, the control cell line. The antitumour evaluation of the compounds separately and in their conjugated form proved that the activity is strongly enhanced in the derivatives containing two redox centres. Thus, our study confirms the efficiency of using A-ring functionalized para-quinones coupled with ortho-quinones to obtain a diverse range of two redox centre compounds with potential applications against cancer cell lines. Here as well, it literally takes two for an efficient tango!